Identification of two flavin monooxygenases from an effluent treatment plant sludge metagenomic library - Singh, Ajit; Chauhan, Nar Singh; Thulasiram, H. V.; Taneja, Vibha; Sharma, Rakesh (Bioresource Technology, 2010)
Oxygenases are useful for the production of many industrially important molecules. Screening of an effluent treatment plant (ETP) sludge metagenomic library identified two clones encoding proteins, B1 and B2, with similarity to putative Flavin monooxygenases from Mesorhizobium loti and Sphingomonas wittichi, respectively. The deduced amino acid sequences show only 20% identity, but both have a paired Rossman fold and a flavin monooxygenase (FMO) motif. B1 and B2 appear to be members of the Flavin-containing monooxygenase and the Baeyer-Villiger monooxygenases subfamilies, respectively. When expressed in Escherichia coli, the two clones produced activities that oxidized indole to a mixture of indigo and indirubin pigments. These results suggest that B1 and B2 have potential as a biocatalyst in indigo/indirubin production. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Indigo; Indirubin; Metagenome; Metagenomic; Monooxygenase

Genome sequence of idiomarina sp strain a28l, isolated from pangong lake, india - Gupta, Hemant Kumar; Singh, Ajit; Sharma, Rakesh (Journal of Bacteriology, 2011)
Idiomarina sp. strain A28L was isolated from the alkaline brackish water of a high-altitude lake, Pangong Lake. Here, we present the draft genome of Idiomarina sp. strain A28L, which contains 2,591,567 bp with a G + C content of 45.5 mol% and contains 2,299 protein-coding genes and 56 structural RNAs.

Genome sequence of rheinheimera sp strain A13L, isolated from pangong lake, india - Gupta, Hemant Kumar; Gupta, Rinkoo Devi; Singh, Ajit; Chauhan, Nar Singh; Sharma, Rakesh (Journal of Bacteriology, 2011)
Rheinheimera sp. strain A13L, which has antimicrobial activity, was isolated from alkaline brackish water of the high-altitude Pangong Lake of Ladakh, India. Here we report the draft genome sequence of Rhienheimera sp. strain A13L (4,523,491 bp with a G + C content of 46.23%). The genome is predicted to contain genes for marinocine and colicin V production, which may be responsible for the antimicrobial activity of the strain.

Genome sequence of nitratireductor aquibiodomus strain RA22 - Singh, Ajit; Jangir, Pramod Kumar; Kumari, Chanchal; Sharma, Rakesh (Journal of Bacteriology, 2012)
The genus Nitratireductor represents nitrate-reducing bacteria from the family Phyllobacteriaceae. Here we report the draft genome sequence of Nitratireductor aquibiodomus strain RA22, which contains 4,592,790 bp, with a G+C content of 61.30%, and has 4,241 protein coding genes.

Genome sequence of the alkaliphilic bacterium nitritalea halalkaliphila type strain LW7, isolated from Lonar Lake, India - Jangir, Pramod Kumar; Singh, Ajit; Shivaji, S.; Sharma, Rakesh (Journal of Bacteriology, 2012)
An alkaliphilic bacterium, Nitritalea halalkaliphila LW7, which belongs to the family Cyclobacteriacae in the phylum Bacteroidetes, was isolated from Lonar Lake in Maharastra, India. Here we announce the draft genome sequence of the type strain LW7, which contains 3,633,701 bp with a G+C content of 48.58%.

Transformation of (+/-)-lavandulol and (+/-)-tetrahydrolavandulol by a fungal strain Rhizopus oryzae - Daramwar, Pankaj P.; Rincy, Raju; Niloferjahan, Siddiqui; Krithika, Ramakrishnan; Gulati, Arvind; Yadav, Amit; Sharma, Rakesh; Thulasiram, Hirekodathakallu V. (Bioresource Technology, 2012)
Biotransformation of an irregular monoterpene alcohol, (+/-)-lavandulol [(+/-)-5-methyl-2-(1-methylethenyl)-4-hexen-1-ol] (I) and its tetrahydro derivative, (+/-)-tetrahydrolavandulol [(+/-)-2-isopropyl-5-methylhexan-1-ol] (II) were studied using a soil isolated fungal strain Rhizopus oryzae. Five metabolites, 2-((3,3-dimethyloxiran-2-yl)methyl)-3-methylbut-3-en-1-ol (Ia), 2-methyl-5-(prop-1-en-2-yl)hex-2ene-1,6-diol (Ib), 2-methyl-5-(prop-1-en-2-yl)hexane-1,6-diol (Ic), 2-(3-methylbut-2-enyl)-3-methylenebutane-1,4-diol (Id), 5-methyl-2-(2-methyloxiran-2-yl)hex-4-en-1-01 (Ie) have been isolated from the fermentation medium and characterized with lavandulol as a substrate. When tetrahydrolavandulol used as a substrate, two metabolites 2-isopropyl-5-methylhexane-1,5-diol (IIa) and 2-isopentyl-3-methylbutane-1,3-diol (lib) have been isolated from the fermentation medium. Biotransformation studies with R. oryzae clearly indicate that the organism initiates the transformation either by hydroxylation at allylic methyl groups or epoxidation of double bond. GC and GCMS analyses indicated that both (R)and (S)-enantiomers of I and II have been transformed into corresponding hydroxylated or epoxy derivatives, when racemic I and II were used as substrates. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biotransformation; Fungus; Lavandulol; Rhizopus oryzae; Tetrahydrolavandulol